Influence Of WhatsApp Broadcast Messages on Interpersonal Relationship Between Youths and Parents (Lead City International Journal of Library, Information & Communication Sciences, 2025)
WhatsApp, a digital platform, with broadcast messaging as one of its features, enables users to send a single message to several contacts at once, promoting effective information transmission.This study examined the influence of WhatsApp broadcast messages on interpersonal relationship between youths and parents. The study defines the problem, first, defining the importance of a good interpersonal relationship between youths and their parents and then going further to investigate the influence of broadcast messages on the interpersonal relationship between youths and parents. The survey research method was employed in this study and questionnaire was used for data collection from the selected 100 respondents. Findings of the study reveal that parents make use of WhatsApp broadcast messages to communicate with their youth children, though, youths see some of these messages as information overload. Findings also reveal that respondents do not feel WhatsApp broadcast messages have improved the depth of communication or relationship between themselves and their parents/children. The study however recommends that both parents and youth should intentionally build strong interpersonal relationship as WhatsApp broadcast messages cannot and should not replace the emotional connections that come from face-to-face conversations.